Comparison of Selected Lactate Threshold Parameters with Maximal Lactate Steady State in Cycling - Hauser, T.; Adam, J.; Schulz, H. (International Journal of Sports Medicine, 2014)
The aim of the present investigation was to compare power at “onset of blood lactate accumulation” (OBLA), “individual anaerobic threshold” (IAT) and “+1.5 mmol ∙ l−1 lactate model” with power in maximal lactate steady state (MLSS) in cycling. However, there is a lack of studies concerning the absolute individual differences between different lactate parameters and MLSS.A total of 57 male participants performed several 30-min constant-load tests to determine MLSS by measuring blood lactate concentration (BLC). Depending on BLC, power was increased or decreased by 10 W in the following 30-min test. For detecting power at different threshold parameters, an incremental test was performed that began at 40 W and increased by 40 W every 4 min.Highly significant correlations were found between OBLA and MLSS: r=0.89 (mean difference −7.4 W); IAT and MLSS: r=0.83 (mean difference 12.4W), “+1.5 mmol ∙ l−1 lactate model” and MLSS: r=0.88 (mean difference −37.4W). On average, the parameters of OBLA and IAT approximate MLSS with no significant differences. The “+1.5 mmol ∙ l−1 lactate model” underestimates MLSS significantly.Based on Bland-and-Altman, the comparison of power of all threshold parameters with power in MLSS shows great individual differences despite the high regression coefficients and low mean differences between these methods.
Keywords: maximal lactate-steady-state; lactate threshold; endurance performance diagnostic; cycling; blood-lactate-concentration